APLIKASI BREAK EVEN POINT PADA PEMBUATAN ROTI Studi Kasus: Usaha Kecil Menengah (UKM) Roti (Rotiku Rotimu) Desa Babakan - Made Wijana; A.A. ALit Triadi; Muhammad Kholiq (Dinamika Teknik Mesin, 2015)
In recent years many companies both micro and macro level national and international emerging. As UKM (Usaha Kecil Menengah) have an important role in opening new jobs and boost economic growth of a region. With the development of business world has been brought towards the increasingly fierce competition. That businesses are required to conduct an economic analysis that can help entrepreneurs to consider actions proposed in choosing the alternatives or strategic decision.This research aimed to analyze the feasibility of the operation of UKM bread (my bread your bread) Babakan Village by using BEP (Break Even Point).Location research Babakan Village, District Cakranegara, West Lombok. By collecting  various kinds of costs of making bread among other fixed costs and variable costs as well as to record income from the sale of bread in a period of 1 year. Examples of fixed costs is the cost of equipment, maintenance costs, the cost of building and examples of variable costs is the cost of raw materials, the cost of operation of the device, the cost of salaries, the cost of packaging.The results of this research indicate that UKM income Bread (my bread your bread) for 1 year is Rp. 912,000,000.00 of the total production of 1.14 million pieces of bread. This UKM bread achieve the BEP (Break Even Point) occurred in the month 4th at a fixed cost is Rp.30,250,733,33 and VC (Variable Cost) is Rp.212,240,114,71 on the amount of bread produced 303114 fruit bread with a TC (total cost) Rp.242,490,848.04. So that UKM Bread (my bread your bread) feasible to be operated. With the increase in the selling price of Rp.850.00 fried bread resulting increase in profit of Rp57,000,000.00 while the selling price of Rp.750.00 fried bread resulted in a decrease in profit of Rp.57,000,000.00 while equally produce 1.14 million pieces bread. By lowering the variable costs, employers can accelerate the achievement of breakeven levels (Break Even Point).